2002
DOI: 10.1038/sj.jhh.1001470
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atorvastatin on aortic pulse wave velocity in patients with hypertension and hypercholesterolaemia: a preliminary study

Abstract: As statins may contribute to plaque stabilisation, it is important to evaluate whether these drugs may modify arterial stiffness. In 23 patients, aged 32-70 years, with hypertension and hypercholesterolaemia, a doubleblind randomised study vs placebo was performed to evaluate whether atorvastatin was able to modify aortic stiffness, measured from aortic pulse wave velocity (PWV), after a 12-week treatment. The results revealed that atorvastatin did not change blood pressure, significantly lowered (Po0.003; o0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 33 publications
2
60
1
2
Order By: Relevance
“…15 Radical reductions in lipid levels may lead to a transient stiffening of arterial walls, because vessels are composed of both soft (lipid-containing) and rigid (sclerotic) tissue. In addition, the ability of fluvastatin and simvastatin to inhibit proliferation and cholesterol biosynthesis in human arterial myocytes is approximately 10-25 times greater than that of atorvastatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Radical reductions in lipid levels may lead to a transient stiffening of arterial walls, because vessels are composed of both soft (lipid-containing) and rigid (sclerotic) tissue. In addition, the ability of fluvastatin and simvastatin to inhibit proliferation and cholesterol biosynthesis in human arterial myocytes is approximately 10-25 times greater than that of atorvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study reported that 12-week atorvastatin treatment worsened PWV in hypertensive hyperlipidaemic patients. 15 The purpose of the present study was to determine the long-term effects of statins on BP control and PWV in hypertensive hyperlipidaemic patients undergoing antihypertensive therapy. Since recent in vivo studies in rabbits 16 and in vitro data [17][18][19] have indicated that hydrophilic and lipophilic statins have different effects on apoptosis, proliferation of vascular smooth muscle cells, and collagen production by vascular smooth muscle cells, in the present study we evaluated the effects of a hydrophilic drug, pravastatin, and two lipophilic drugs, simvastatin and fluvastatin, on the PWV of hypertensive patients with high serum cholesterol levels.…”
Section: Introductionmentioning
confidence: 99%
“…4 In fact, a literature search revealed that other investigators using this instrument have also measured unreasonably high aortic PWVs. [5][6][7] It appears the problem lies with the error in estimation of the propagation distance of the traveling pulse. The manufacturer recommends the use of the absolute distance between the 2 transducers as the propagation distance.…”
Section: Errors In Estimating Propagation Distances In Pulse Wave Velmentioning
confidence: 99%
“…Accordingly, treatment with statins, medicines with recognized pleiotropic anti-inflammatory properties has been shown to reduce pulse wave velocity. 7 In this issue of the Journal of Human Hypertension, Marketou et al 8 report extremely strong correlations between the expression of angiopoietins' mRNA by CD14 þ monocytes and the elastic behaviour of both elastic type and muscular type arteries. In fact, such amazingly strong correlations (r up to 0.95) are extremely rare in biological sciences and must indicate direct link between the factors analysed.…”
mentioning
confidence: 99%